2014
DOI: 10.1038/srep07590
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonds in Al2O3 as dissipative two-level systems in superconducting qubits

Abstract: Dissipative two-level systems (TLS) have been a long-standing problem in glassy solids over the last fifty years, and have recently gained new relevance as sources of decoherence in quantum computing. Resonant absorption by TLSs in the dielectric poses a serious limitation to the performance of superconducting qubits; however, the microscopic nature of these systems has yet to be established. Based on first-principles calculations, we propose that hydrogen impurities in Al2O3 are the main source of TLS resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…2(a) for the most stable V O model. As for crystalline oxides, [8][9][10][11][12] the neutral and the +2 charge states are the most stable ones with a +2/0 charge transition level occurring in the band gap of a-Al 2 O 3 at ∼5 eV from the VBM.…”
Section: E Qmentioning
confidence: 99%
See 1 more Smart Citation
“…2(a) for the most stable V O model. As for crystalline oxides, [8][9][10][11][12] the neutral and the +2 charge states are the most stable ones with a +2/0 charge transition level occurring in the band gap of a-Al 2 O 3 at ∼5 eV from the VBM.…”
Section: E Qmentioning
confidence: 99%
“…[1][2][3][4][5] For this reason, native defects in Al 2 O 3 have been the subject of extensive experimental and theoretical investigations aiming at verifying the presence of deep-level traps in the dielectric. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The vast majority of theoretical studies performed so far have focused on crystalline phases of Al 2 O 3 . However, Al 2 O 3 in MOS devices is usually deposited via atomic layer deposition, which results in an amorphous phase with electronic properties differing considerably from those of crystalline phases.…”
mentioning
confidence: 99%
“…In recent years bulk defects have been generally ruled out as the dominant source, and the search has focused on surfaces and interfaces [2, 3]. Despite a wide range of theoretical models [4, 5, 6,7,8,9,10,11,12] and experimental efforts [2,13,14,15], the origin of these surface TLS still remains largely unknown, making further mitigation of TLS induced decoherence extremely challenging.Here we use a recently developed [16] on-chip electron spin resonance (ESR) technique that allows us to detect spins with a very low surface coverage. We combine this technique with various surface treatments specifically to reveal the nature of native surface spins on Al 2 O 3the mainstay of almost all solid state quantum devices [1].…”
mentioning
confidence: 99%
“…Similarly, a wide range of models seek to explain the electrically coupled TLSs in resonators and charge qubits where the latest results indicate similar mechanisms at interfaces [2, 3, 6,12,14]. Ab inito studies have suggested several possible candidates for charge coupled TLS, such as hydrogen and hydroxyl defects [5], or tunnelling of protons [11].To shed more light on the nature of noise and decoherence in Al 2 O 3 -based devices we use on-chip electron spin resonance (ESR) spectroscopy in combination with various surface treatments. ESR is a non-destructive technique used to probe the nature and concentration of paramagnetic centers and their interaction with the environment.…”
mentioning
confidence: 99%
“…Thus TLSs are found as defects in various dielectric structures: deposited insulating films [1,5,6], Josephson Junction (JJ) tunneling barriers [1,7,8], imperfect interfaces between superconducting films with crystalline substrates [9], and the native oxides on materials [10]. Recent modeling has predicted possible structures and values for the TLS dipole moment [11][12][13]. While these TLSs are generally known to be charged atomic configurations that spatially tunnel, their microscopic structure and elemental composition are generally unknown.…”
mentioning
confidence: 99%